Definite photon deflections of topological defects in metasurfaces and symmetry-breaking phase transitions with material loss - Chong Sheng (Nature Portfolio, 2018)
Photonic structures can be used to simulate fundamental physical phenomena like the optical analog of gravity. Here, the authors use metasurface-engineered waveguides to emulate the optical effects of a topological defect on space-time.